Divergent synthesis of oxepino-phthalides and [5,5]-oxaspirolactones through [2+2+2]- and [2+3]-annulation of alkynyl alcohols with a-ynone-esters - Kambale, Digambar A.; Borade, Balasaheb R.; Vinodkumar, Ramavath; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Unmasking the synthetic potential of alkyne functional group of alkynyl alcohols as surrogates of carbonyl compounds, herein we present the first Bronsted acid (TfOH)-catalyzed [2 + 2 + 2]-annulation of 4-pentyn-1-ols (possessing terminal alkyne) with a-ynone-esters to access tricyclic tetrahydro-oxepino-phthalides. Besides, an unprecedented synthesis of a-acetoaryl or a-alkynyl [5,5]-oxaspirolactones has been demonstrated by employing 4-pentyn-1-ols (possessing an internal alkyne) as an annulation partner, which proceeds through a divergent [2 + 3]-annulation pathway.

Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.

Divergent access to α-carbonyl-α′-vinyl sulfoxonium ylides and polysubstituted furans from β-ketosulfoxonium ylides and ynone-esters - Ingale, Sudhir R.; Sahu, Manas Ranjan; Borade, Balasaheb R.; Gamidi, Rama Krishna; Kontham, Ravindar (Journal of Organic Chemistry, 2025)
Here, we describe the synthesis of novel alpha-carbonyl-alpha `-vinyl sulfoxonium ylides under ambient, catalyst-free, and additive-free conditions, demonstrating broad substrate scope and scalability using beta-ketosulfoxonium ylides and alpha-ynone-esters. Furthermore, these ylides serve as versatile intermediates for the synthesis of highly substituted furans via Br & oslash;nsted acid (p-TsOH) catalysis at 130 degrees C. This approach offers key advantages, including wide substrate compatibility, divergent product formation from common precursors, gram-scale feasibility, and good to excellent yields.